Crystal Structure of Nd10.67Pt4O24, a New Neodymium Platinate - Fjellvåg, Øystein Slagtern; Fjellvåg, Helmer; Hessevik, Julie; Sjåstad, Anja Olafsen; Steciuk, Gwladys (ACS omega, 2025)
A new platinate was recently discovered when Nd2O3 was explored as a platinum capture material in the Ostwald process, formed by a direct reaction between gaseous PtO2 and Nd2O3. The crystal structure of this new platinate and its composition, Nd10.67Pt4O24, are here reported for the first time. The compound is synthesized either by a direct reaction between PtO2(g) and Nd2O3 or by the citric acid chemical route. Based on 3-dimensional electron diffraction data and Rietveld refinement of high-resolution synchrotron and neutron powder diffraction data, we describe its crystal structure in space group I41/a. The compound is structurally related to the Ln11-x Sr x Ir4O24 (Ln = La, Pr, Nd, and Sm) phases with a double perovskite (A2BB'O6)-like crystal structure with A-site cation deficiency. Owing to the fixed oxidation state of Pt(IV), two of the four Nd sites are partly occupied to provide charge neutrality, with Nd4 taking a split position. On heating, Nd10.67Pt4O24 decomposes into Nd2O3 and Pt. A plateau in the thermogravimetric curves measured in 33 vol % O2 in N2 indicates the presence of an intermediate Pt(II) phase at around 960 °C, probably isostructural with La4PtO7.